Pengaruh Tingkat Kemandirian, Kesejahteraan Masyarakat dan Kekayaan Pemerintah Daerah Terhadap Pengungkapan Informasi Keuangan Pada Website Resmi Pemerintah Daerah (Studi Kasus Pada Pemerintah Daerah di Pulau Kalimantan Tahun 2019-2020) - Aliffia Nur Indaryani; Sri Rahayu (UNIVED Press, 2023)
The This study aims to examine the influence of the level of independence, community welfare and regional wealth on the disclosure of financial information on the official website of the local government. The data used in this study are secondary data. This research uses quantitative methods. The sampling technique in this study used saturated samples this study is the Regional Government on the island of Kalimantan in 2019-2020. The data analysis model used by this study is logical regression analysis using SPSS Version 23 software. The results showed that the level of independence, community welfare and regional wealth simultaneously had a significant impact on the positive direction of the disclosure of financial information on the official website of the local government. Meanwhile, partially the level of independence, community welfare and regional wealth has a significant positive effect on the disclosure of financial information on the official website of the local government